AN ANALYSIS OF INDEPENDENT CHARACTER OF PRIMARY SCHOOL STUDENTS IN LEARNING FROM HOME DURING THE COVID-19 PANDEMIC (A Case Study at SD Muhammadiyah 8 Surabaya) - Umar Haiq; Badruli Martati; fajar setiawan (Widyagogik, 2020)
This research aims to determine the process of the development of the independent character of elementary school students in learning from home during the Covid-19 pandemic at SD Muhammadiyah 8 Surabaya in grades 4, 5, and 6 by referring to the achievement of indicators of independent character values and the obstacles that arise in their achievement. By using a qualitative approach, the discussion will be presented in a descriptive explanation. The research subjects are 99 upper-class student respondents (4, 5, and 6) at SD Muhammadiyah 8 Surabaya. The research is carried out only by taking data on March, April, and May 2020 as the research scope. In this research, data are collected giving online questionnaire observation techniques to students, accompanied by parents, and having direct interviews with class teachers and subject teachers. The discussion in this research shows that the level of development of the independent character of students has been built with an average of being in the category of culture and development even though there are still obstacles because they require assistance, either directly or indirectly from parents and teachers.Keywords: Character, Independence, Covid-19 Pandemic